Sadd al-Dzari’ah as a Preventive Paradigm for SDGs-Based Waste Governance in Bandar Lampung City - Gesit Yudha; Agus Hermanto; Abdul Azis; Maulana Bagus Rahmat (Profetika: Jurnal Studi Islam, 2027)
Objective: This study aims to examine how the Sadd al-Dzari’ah principle of Islamic legal theory can be reconstructed into a preventive, SDGs-based governance model for urban waste management in Bandar Lampung City. Theoretical framework: The study draws on Sadd al-Dzari’ah and maqāṣid al-Sharī‘ah as normative Islamic legal foundations, combined with New Institutionalism theory to explain the facilitative, catalytic, and regulatory roles of local government in environmental governance. Literature review: Existing studies on Islamic values and waste management have largely examined individual and community behavioral change, with limited attention given to how such values can be systematically institutionalized within local government policy or connected to the Sustainable Development Goals (SDGs) framework. Methods: This qualitative field research employs a descriptive-exploratory case study approach in Bandar Lampung City, using observation, documentation, and interviews with stakeholders of the City Environmental Agency, analyzed through content analysis and social theory analysis. Results: The findings show that the current waste management policy in Bandar Lampung City remains reactive and downstream-oriented; applying Sadd al-Dzari’ah principles allows its reconstruction into an upstream-based preventive model encompassing source segregation, strengthened preventive regulation, community participation, and industrial waste control. Implications: The study implies that Islamic normative principles can be operationalized as a systemic model of public environmental governance, helping local governments align waste management policy with SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action). Novelty: Its novelty lies in integrating Sadd al-Dzari’ah with New Institutionalism theory to explain how Islamic ethical-legal values can be embedded in the facilitative, catalytic, and regulatory functions of local government, moving the discourse beyond prior studies that treat religious environmental ethics solely as a matter of individual moral education.